Lamy of Santa Fe his life and times - Horgan, Paul (Farrar, Straus, & Giroux New York, 1975)
Recounts the life and works of Juan Bautista Lamy, first archbishop of Santa Fe and pioneer civilizer of the American Southwest
43772
Keywords: Lamy, John Baptist -- 1814-1888; Southwest; Bishop; Catholic Church; New Mexico